Management of Biochemical Recurrence after Primary Localized Therapy for Prostate Cancer - Darwish, Oussama M.; Raj, Ganesh V. (Frontiers in Oncology, 2012)
Clinically localized prostate cancer is typically managed by well established therapies like radical prostatectomy, brachytherapy, and external beam radiation therapy. While many patients can be cured with definitive local therapy, some will have biochemical recurrence (BCR) of disease detected by a rising serum prostate-specific antigen (PSA). Management of these patients is nuanced and controversial. The natural history indicates that a majority of patients with BCR will not die from prostate cancer but from other causes. Despite this, a vast majority of patients with BCR are empirically treated with non-curable systemic androgen deprivation therapy (ADT), with its myriad of real and potential side effects. In this review article, we examined the very definition of BCR after definitive local therapy, the current status of imaging studies in its evaluation, the need for additional therapies, and the factors involved in the decision making in the choice of additional therapies. This review aims to help clinicians with the management of patients with BCR. The assessment of prognostic factors including absolute PSA level, time to recurrence, PSA kinetics, multivariable nomograms, imaging, and biopsy of the prostatic bed may help stratify the patients into localized or systemic recurrence. Patients with low-risk of systemic disease may be cured by a salvage local therapy, while those with higher risk of systemic disease may be offered the option of ADT or a clinical trial. An algorithm incorporating these factors is presented.